Design And Implementation Of An Ev-Oriented Das-Integrated System With Lifepo4 Battery Backup And Real-Time Performance Analysis (International Journal of Environmental Sciences, 2025)
This paper presents the design, development, and performance analysis of a real-time solar tracking system inte- grated with a Data Acquisition System (DAS), Maximum Power Point Tracking (MPPT) algorithm, and Lithium Iron Phos- phate (LiFePO4) battery storage. The proposed system utilizes a microcontroller-based DAS unit to maximize solar energy capture through dynamic panel orientation and track environmental parameters in real time. A custom-designed MPPT charge controller ensures efficient power conversion, while the energy is stored in a high-efficiency LiFePO4 battery (IFR32700N60, 6000mAh, 3.2V). The hardware integrates a bipolar stepper motor driver for panel tilt adjustment, monitored via a PIC-based embedded controller and RTC for daylight tracking. A potential divider-based current sensor monitors the load dynamics, while a temperature-stable OP-AMP filter design refines signal integrity. Experimental results validate system efficiency through 12 time- series plots (voltage, current, and power across PV modules), extracted from MATLAB and Excel-based post-processing. The solution is modular, programmable, cost-effective, and highly adaptable for smart-grid and off-grid solar applications.